2001
DOI: 10.1093/emboj/20.17.4753
|View full text |Cite
|
Sign up to set email alerts
|

NRG1, a repressor of filamentous growth in C.albicans, is down-regulated during filament induction

Abstract: contributed equally to this workIn response to a variety of external signals, the fungal pathogen Candida albicans undergoes a transition between ellipsoidal single cells (blastospores) and ®la-ments composed of elongated cells attached end-toend. Here we identify a DNA-binding protein, Nrg1, that represses ®lamentous growth in Candida probably by acting through the co-repressor Tup1. nrg1 mutant cells are predominantly ®lamentous under non-®lament-inducing conditions and their colony morphology resembles that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
332
3
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(361 citation statements)
references
References 50 publications
16
332
3
4
Order By: Relevance
“…In detail, small GTPase RAS1 activates cAMP, which promotes the PKA‐mediated activation of transcription factor EFG1 , which in turn regulates hyphae‐specific genes, such as ALS3 , HWP1 , and ECE1 , and thus, modulates hyphal formation (Leberer et al ., 2001). RBT1 (repressed by TUP1 ) encodes cell surface proteins that are regulated by Tup1, which exhibits high similarity to HWP1 (Braun et al ., 2001). Here, we suggest 7‐benzyloxyindole inhibits biofilm formation by modulating Ras‐cAMP‐Efg1 signalling pathway genes ( HWP1 , RBT1 and ECE1 ), which are strongly associated with long‐term hyphal maintenance, and thus, reducing hyphal development.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, small GTPase RAS1 activates cAMP, which promotes the PKA‐mediated activation of transcription factor EFG1 , which in turn regulates hyphae‐specific genes, such as ALS3 , HWP1 , and ECE1 , and thus, modulates hyphal formation (Leberer et al ., 2001). RBT1 (repressed by TUP1 ) encodes cell surface proteins that are regulated by Tup1, which exhibits high similarity to HWP1 (Braun et al ., 2001). Here, we suggest 7‐benzyloxyindole inhibits biofilm formation by modulating Ras‐cAMP‐Efg1 signalling pathway genes ( HWP1 , RBT1 and ECE1 ), which are strongly associated with long‐term hyphal maintenance, and thus, reducing hyphal development.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, they found that the expression of CaFTR1 and CaCFL2 was increased by 16-and 61-fold, respectively. They also found significantly elevated levels of expression of these two genes in a strain with a deletion of CaNRG1, which encodes a DNA-binding subunit for the Tup1p-Ssn6p repressor complex (42)(43)(44). This result prompted us to examine whether CaTup1p also regulates the expression of CaARN1.…”
Section: Iron-responsive Regulation Of Caarn1mentioning
confidence: 98%
“…Less attention has been paid to factors that regulate the hyphal-to-yeast transition, such as the hyphal repressors Nrg1 or Tup1 [31][32][33], or to factors that are important for maintenance or extension of hyphal growth, for example Cln1, Pes1, Eed1 or Ume6 [34][35][36][37][38]. These factors not only govern morphology, but also regulate morphologyassociated genes, for example, HWP1, SOD5, SAP4-6 or ALS3, the expression of which is linked to hyphal growth under most conditions.…”
Section: Proposed Roles Of Yeast and Hyphal Morphologies Of C Albicansmentioning
confidence: 99%